Drug use and perceived social support in a sexual minority - Izabel Cristina de Souza; Tainan Maria Cruz Lopes Tavares; Gilmara de Lucena Beserra; Antônio José Lima de Araújo Júnior; Weslley Monteiro Amora Sousa; Samila Gomes Ribeiro; Paula Renata Amorim Lessa Soares; Ana Karina Bezerra Pinheiro (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Aim To evaluate the perception of social support in a sexual minority and to associate it with the risk of drug addiction. Method Cross-sectional study, with 254 self-declared gay, bisexual, lesbian, or transsexual participants in the city of Fortaleza, between October and December 2019. Data analyzed by descriptive statistics and likelihood ratio tests. Results Most were satisfied with social support between low and medium (74.4%). The most commonly used drugs were alcohol (91.5%), tobacco (67.4%) and marijuana (66.9%). Assessing the risk of addiction, 28.7% scored it as low, 46.9% as moderate, and 9.8% as high risk. There was significance between satisfaction of social support and years of study. Conclusion We found a level of satisfaction between low and medium, and it was possible to report the most consumed drugs. There was no association between social support and drug use, although the weaknesses and strengths of social support have been highlighted.